Integration Of Spa Tio- Temporal Analysis Of Rainfall And Community Information System To Reduce Landslide Risk In Indonesia - Sudibyakto Sudibyakto (Indonesian Journal of Geography, 2008)
Indonesia is vulnerable to many type of disasters including natural and anthropogenic disasters. Indonesian seasonal rainfall also shows inter annual variation. Sediment-related disaster such as landslide is the mostji-equent disaster occurred and significantly was impacted to natural, human. and social environment. Although. many disaster mitigation e.Oorts have been conducted to reduce disaster risk there are still urgently need to improve the early 1varning .ỹstem by communicating the risk into local community. Integration qf spatialtemporal analysis qf rainfall and disaster management information !o~vstem would be required to improve the better disaster management in Indonesia. Application of Disaster A1anagement Information System in the study area will presented including evacuation map that used by the local community.